The World on a Fingernail: An Unknown Byzantine Map, Planudes, and Ptolemy - Pontani, Filippomaria (Traditio, 2010)
MS Vat. Gr. 915 (bombyc., ca. 266 × 170 mm, 258 fols.) is a most interesting collection of archaic, classical, and Hellenistic Greek poetry (from Homer and Hesiod to Pindar, from Theocritus and Lycophron down to Moschus and Musaeus) put together during the early Palaeologan Renaissance, more exactly between the last years of the thirteenth century and 1311 (the terminus ante quem is provided by the subscription on fol. 258v). The contents of this codex as well as the textual facies of several of its items have led various scholars, each from a different perspective, to conclude that it was produced in the circle of Maximus Pianudes, the most outstanding Greek scholar of his age (of which he is also in a sense the “eponymous hero”); more on this will be said below in §3.